Pembangunan sistem maklumat kawalan kadaster bagi menyokong sistem kadaster berkoordinat Semenanjung Malaysia - Lim, Lee Won (2003)
The current use of cadastral surveying system in Malaysia has been able to satisfy mapping and title survey requirements. The Coordinated Cadastral System (CCS) is a system that specifies and legalizes each pair of coordinates that are assigned to the boundary marks of a cadastral lot. The information of Cadastral Control Network is important for State Digital Cadastral Database (SDCDB) adjustment and coordinate registration. The high accuracy Cadastral Control Network has been established. However, CCS is still in development stage. As a results, Cadastral Control Network datasets are still store in hardcopy form which are not arrange and manage properly. These will cause difficulties to search related Cadastral Control Information and the development of National Digital Cadastral Database (NDCDB). The aim of this research is to develop a Cadastral Control Information System which manage all the data of Cadastral Control Network in homogen reference system for the 5 x 10 km Wilayah Persekutuan and 40 x 40 km Melaka-Johor study area with ArcInfo Version 8.0.2. This Cadastral Control Information System can be used for the NDCDB development and provides a common reference system for both cadastre and topography data. The scope of this study covers the user requirement analysis, data collection, data processing, database design and as well as the user interface system development. With the development of this system, problems in storage, management and data analysis for Cadastral Control Information can be overcome. In addition, tasks such as data editing, searching and displaying can be done more easily, faster and effectively.